Recognition and the Resurrection Appearances of Luke 24 - Thompson, Alexander Phillip (De Gruyter, 2023)
How are the resurrection appearances of Luke's Gospel shaped to offer a climax to the narrative? How does this narrative conclusion compare to the wider ancient literary milieu? Recognition and the Resurrection Appearances of Luke 24 proposes that the ancient literary technique of recognition offers a compelling lens through which to understand the climatic role of the resurrection appearances of Jesus as depicted in Luke 24. After presenting the development of recognition in ancient Jewish and Greco-Roman literature, Thompson demonstrates how Luke 24 deploys the recognition tradition to shape the form and function of the resurrection appearances. The ancient recognition tradition not only casts light on various literary and theological features of the chapter but also shapes the way the appearances function in the wider narrative. By utilizing recognition, Luke 24 generates cognitive, affective, commissive, and hermeneutical functions for the characters internal to the narrative and for the audience. The result is a compelling climax to Luke's Gospel that resonates with Luke's wider literary and theological themes. This work offers a compelling analysis of the Luke's Gospel in the ancient literary context in light of the ancient technique of recognition that will appeal to those interested in narrative approaches to the New Testament or the interpretation of the New Testament in the wider literary milieu
Description based on online resource; title from PDF title page (publisher's Web site, viewed 28. Feb 2023)
Keywords: Bibel -- Lukasevangelium -- 24; Auferstehung; Lukasevangelium; Narrative Exegese; Neues Testament; RELIGION / Biblical Criticism & Interpretation / New Testament; Wiedererkennen -- Motiv